CHEF'S CREATIVITY AND THE MODERN GASTRONOMY CONSUMPTION - Rita Cássia Ribeiro; Rita Cássia Marques; Edgar Gastón Jacobs Flores Filho (Universidade do Estado do Rio de Janeiro, 2016)
In this essay we intend to discuss meals modern commensality, with the backdrop of gastronomy and the chefs' work. These professionals, by designing menus, enable people to eat whatever they want and to try new flavors and favor the incorporation of new eating modes. Therefore, the aim was to investigate and discuss the role of chefs' creativity in preparing menus and the impacts of this action on food consumption. In this investigation, semi-structured interviews were conducted with chefs of à la carte restaurants located in the south central region of Belo Horizonte, Minas Gerais state, Brazil. The interviews were conducted by saturation of information and the processing and interpretation of results allowed to establish a relationship between the content expressed in the discourse and the scientific literature. The chefs' creative process and therefore their influence on new modes of contemporary eating may indicate a new route for studies related to eating behaviors. It was found that, in times of eating modernity, creativity, personal and professional experiences and the excitement caused by it in clients are foundations of the chefs' work. DOI: 10.12957/demetra.2016.15443